Pengaruh Daya Beli Dan Kualitas Pelayanan Terhadap Tingkat Penjualan Toko Online Fitra Shopp Di Kabupaten Lampung Timur: Pendahuluan, Hasil Penelitian, Pembahasan, Bahan dan Metode, Kesimpulan, Referensi - Eemy Nurbaety; Rohmadi (Business Finence Analyst Co.,, 2023)
Competition in the business world today is increasingly fierce. This is also felt by the online shop Fitra Shopp. This shop certainly has a target to increase sales in its business, namely by implementing the right marketing strategy. For this strategy to be successful, the store must know the indicators that can influence sales levels. Sales levels can be created through increased purchasing power and quality service. The aim of this research is to analyze the influence of purchasing power and service quality on the sales level of the Fitra Shopp online store in East Lampung Regency. This type of research is quantitative research, using SPSS version 21 tools. The results of this research show that all independent variables tested have a positive and significant effect on sales levels. Based on the research results, it can be seen that: (1) the purchasing power variable has a positive and significant effect on the sales level; (2) the service quality variable has a positive and significant effect on the sales level; and (3) the purchasing power and service quality variables simultaneously have a significant positive effect on the sales level.